Characterization and experimental investigation of rheological behavior of oxide nanolubricants. (18th August 2021) - Gupta, Harsh; Rai, Santosh Kumar; Kuchhal, Piyush; Anand, Gagan
Abstract: Nanolubricants are nano fluid, colloidal nanoparticle suspension, which are specially used for machine lubrication of the engine. Nanolubricants exhibit special tribological properties that have potential applications in mainly automotive industries. Performance of an engine is a function of the lubricant being used. A study of rheological behaviors of nanolubricants has been beneficial in understanding the influence of nanolubricants on shear rate and shear stress. This study is concerned with characterization and rheological behavioral studies of five nanolubricants, i.e., SnO2, TiO2, Fe3 O4, CuO and ZnO mixed with engine oil at 1% volume by weight concentration. In this study, the result showed that the shear rate was independent of viscosity confirming the Newtonian behavior of these nanolubricants. Non-linear decrease in the shear viscosity, with the rise of the temperature, was observed as well from the result. This non-linear behavior observed in these nanolubricants open up the potential for high-temperature application of these nanolubricants which would greatly benefit automotive industries.